Contemporary documentary - Marcus, Daniel 1958-; Kara, Selmin (Routledge, 2016)
Contemporary Documentary covers documentary film, television, video, and new media. The essays address the emerging forms, popular genres, and innovative approaches of the digital era. The anthology highlights geographically and thematically diverse examples of documentaries that have expanded the scope and impact of non-fiction cinema and captured the attention of global audiences over the past three decades. It also explores the experience of documentary today, with its changing dynamics of production, collaboration, distribution, and exhibition, and its renewed political and cultural relevance. The twelve chapters - featuring engaging case studies and written from a wide range of perspectives including film theory, social theory, ethics, new media, and experience design